In vitro diagnostic methods of Chagas disease in the clinical laboratory: a scoping review - Ascanio, Luis C.; Carroll, Savannah; Paniz-Mondolfi, Alberto; Ramírez, Juan David (Frontiers in Microbiology, 2024)
Background Chagas disease (CD), caused by Trypanosoma cruzi, is a global health concern with expanding geographical reach. Despite improved and accessible test methods, diagnosing CD in its various phases remains complex. The existence of clinical scenarios, including immunosuppressed patients, transplant-related CD reactivation, transfusion-associated cases, and orally transmitted acute infections, adds to the diagnostic challenge. No singular gold standard test exists for all phases, and recommendations from PAHO and the CDC advocate for the use of two serological methods for chronic CD diagnosis, while molecular methods or direct parasite detection are suggested for the acute phase. Given the complexity in the diagnostic landscape of CD, the goal of this scoping review is to characterize available diagnostic tests for CD in the clinical laboratory. Methods A literature search in PubMed was conducted on studies related to In vitro diagnosis (IVD) in humans published in English, Spanish, or Portuguese language as of 28 August 2023, and extended backward with no predefined time frame. Studies underwent title and abstract screening, followed by full-text review. Studies included were classified based on the diagnostic method used. Test methods were grouped as serological, molecular, and other methods. Performance, availability, and regulatory status were also characterized. Results Out of 85 studies included in the final review, 115 different tests were identified. These tests comprised 89 serological test types, 21 molecular test types, and 5 other test methods. Predominant serological tests included ELISA (38 studies, 44.70%), Rapid tests (19 studies, 22.35%), and chemiluminescence (10 studies, 11.76%). Among molecular tests, Polymerase Chain Reaction (PCR) assays were notable. Twenty-eight tests were approved globally for IVD or donor testing, all being serological methods. Molecular assays lacked approval for IVD in the United States, with only European and Colombian regulatory acceptance. Discussion and conclusion Serological tests, specifically ELISAs, remain the most used and commercially available diagnostic methods. This makes sense considering that most Chagas disease diagnoses occur in the chronic phase and that the WHO gold standard relies on 2 serological tests to establish the diagnosis of chronic Chagas. ELISAs are feasible and relatively low-cost, with good performance with sensitivities ranging between 77.4% and 100%, and with specificities ranging between 84.2% and 100%. Molecular methods allow the detection of specific variants but rely on the parasite’s presence, which limits their utility to parasitemia levels. Depending on the PCR method and the phase of the disease, the sensitivity ranged from 58.88 to 100% while the mean specificity ranged from 68.8% to 100%. Despite their performance, molecular testing remains mostly unavailable for IVD use. Only 3 molecular tests are approved for IVD, which are available only in Europe. Six commercial serological assays approved by the FDA are available for blood and organ donor screening. Currently, there are no guidelines for testing CD oral outbreaks. Although more evidence is needed on how testing methods should be used in special clinical scenarios, a comprehensive approach of clinical assessment and diagnostics tests, including not IVD methods, is required for an accurate CD diagnosis.